Media Framing of Rohingya Muslims: A Comparative Analysis of Western, Middle Eastern, and Southeast Asian Media - Contesa, Yenis; Sahide, Ahmad (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
The Rohingya, a Muslim minority group in Myanmar, have long suffered systematic discrimination, persecution, and violence that has culminated since 2017. The Myanmar government refuses to grant citizenship to the Rohingya, considering them illegal immigrants from Bangladesh, even though they have lived in Myanmar for generations. To highlight the complex relationship between media, geopolitics, and public opinion formation, this research seeks to analyze potential biases and contrasting narratives between Western, Middle Eastern, and Southeast Asian media opinions on Rohingya Muslims. To examine the portrayal of the Rohingya as “refugees”, “victims of violence”, and “rejects”, this study used NVIVO 14 by analyzing 120 news stories, consisting of 40 stories from Western media (CNN and BBC News), 40 from Middle Eastern media (Al Jazeera and Alarabiya News), and 40 from Southeast Asian media (Kompas and The Star). The results showed that Western media tended to frame the Rohingya as victims of violence, Middle Eastern media highlighted the plight of refugees in some countries, while Southeast Asian media highlighted the theme of resistance to their arrival. The analysis also found that the media tended to use neutral sentiments, although bias was detected in certain narrative and framing choices. This research contributes to discourse studies by emphasising the importance of understanding framing biases in shaping public opinion and suggests further analysis that includes levels of semiotics and critical discourse to reveal the depth of media narratives on the Rohingya.